A case of auteur cinema in a changed cultural context: “Funny Games” (1997) and “Funny Games, US” (2007) by Michael Haneke - Aleksandra Biernacka (Journal of Comparative Research in Anthropology and Sociology, 2012)
The article is a case study of a cross-cultural auteur film-remake by Michael Haneke of his earlier film: Funny Games, US (2007) and Funny Games (Austria 1997), that is a part of a PhD project devoted to the cross-cultural film remakes. The case of the Funny Games, US although an exact frame-by-frame repetition, shows a significant alteration of meanings that arise out of the changed cultural context a remade film is destined to operate in. The different set of ideas and historical experiences modify a seemingly universal for the Western culture problem the film attempts to discuss with. Through cultural, hermeneutical analysis of a particular basic assumptions the films’ discourse is formed on, the author shows how given points lose their adequacy and relevance leading to a final failure of the communication process and a lack of expected reaction to the US-version-of-the-film’s efforts at provoking a serious debate.